Nursing Care Analysis of Pursed Lips Breathing and Semi-Fowler for Pulmonary Tuberculosis Families in Ragunan - Desfara Anggreani; Intan Asri Nurani (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Pulmonary tuberculosis was an infectious disease caused by Mycobacterium tuberculosis which infected the lung organs. Appropriate actions performed by nurses included pursed lips breathing therapy and the semi-Fowler position to optimize tidal volume and help facilitate the airway to the lungs. This case study aimed to increase the ability to analyze nursing care through pursed lips breathing interventions and the semi-Fowler position in families with pulmonary tuberculosis using a descriptive method on two families for three consecutive days with a duration of two minutes. Data collection used assessment sheets and a pulse oximeter. There was an increase in oxygen saturation levels from in Mr. SpO₂ = 90% ke SpO₂ = 95% M’s family and from SpO₂ = 91% ke SpO₂ = 97% in Mr. T’s family after the therapy was provided. Pursed lips breathing therapy and the semi-Fowler position proved effective for increasing oxygen saturation levels in pulmonary tuberculosis patients and the quality of independent family health. Nurses were able to conduct home visits directly and periodically to ensure the progress of the activities. Keywords: Pulmonary Tuberculosis, Pursed Lips Breathing, Semi-Fowler.